Family Resilience in Context: A Conceptual Framework for Understanding Infidelity in Nigerian Military Families - Abdulrazaq O. Kilani; Ibrahim Suberu; Sulaiaman Musa Aliyu (MD Research Center, 2026)
Marital infidelity within military families remains an underexplored issue in non-Western contexts despite its implications for family wellbeing and organizational resilience. This study develops a context-sensitive conceptual understanding of the psychological, social, and institutional consequences of infidelity among Nigerian military families through an integrative review of interdisciplinary literature. The thematic synthesis suggests that infidelity extends beyond a private marital issue to become a multidimensional phenomenon shaped by military occupational demands, collectivist family structures, religious values, and institutional support systems. Psychological distress, family instability, community stigma, and organizational barriers emerge as interconnected dimensions influencing both family resilience and military effectiveness. By integrating Walsh’s Family Resilience Theory, Social Exchange Theory, and the Maq??id al-Shar??ahframework, this study proposes a culturally grounded conceptual model that explains how resilience is constructed through interactions among psychological adaptation, kinship networks, faith-based coping, and institutional responses. The review contributes to military family scholarship by extending resilience theory beyond predominantly Western perspectives while informing culturally responsive family welfare policies in military settings.